Ms. Marvel. - Reed, Brian 1973- (Marvel Comics, 2007)
Carol Danvers has been known by many names; most recently, she's called herself Captain Marvel. Now, however, she re-adopts the name Ms. Marvel and decides that it's time she lived up to the name. On the way to earning the name, she settles a score with the evil Brood, prevents an invading alien from destorying the Earth, and fights off a mad magician from another reality.